2007
DOI: 10.1203/pdr.0b013e3180459f5b
|View full text |Cite
|
Sign up to set email alerts
|

T Helper 1 Background Protects Against Airway Hyperresponsiveness and Inflammation in Guinea Pigs With Persistent Respiratory Syncytial Virus Infection

Abstract: A family history of allergy has been implicated in children who develop post-bronchiolitis wheezing and asthma. In a guinea pig model of respiratory syncytial virus (RSV) lung infection, we evaluated the role of host Th1 background (either genetic or induced) on the development of a persistent infection, nonspecific airway hyperresponsiveness (AHR) and airway inflammation. Allergy resistant/T helper 1 (Th1)-skewed strain 2 guinea pigs (STR2) and cytosine phosphate guanine oligodeoxynucleotides (CpG-ODN) (Th1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This finding suggested a possible role of RSV persistence in the pathogenesis of postbronchiolitis sequelae [22] [23]. No similar studies appear to be reported about PIV3, so referring to this criterion and to avoid causing pneumonia in guinea pigs, the dose of PIV3 that we selected was 3.3 × 10 5 PFU/mL.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested a possible role of RSV persistence in the pathogenesis of postbronchiolitis sequelae [22] [23]. No similar studies appear to be reported about PIV3, so referring to this criterion and to avoid causing pneumonia in guinea pigs, the dose of PIV3 that we selected was 3.3 × 10 5 PFU/mL.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been shown in a guinea pig model of RSV persistence where, although persistence was observed whether there was a T H 1 or T H 2 skew in immune response, there were lower viral loads in the T H 1 skewed animals. 69 There are other mechanisms that RSV may use to evade the host's immune response. The nonstructural proteins (NS1 and NS2) have been shown to antagonize IFN-␣, IFN-␤, and IFN-responses 70,71 -this would result in impaired antiviral immunity and possible persistence of virus.…”
Section: Mechanisms Of Persistence Of Rsv In Copd Patientsmentioning
confidence: 99%
“…After initial work establishing that RSV protein and genome could persist in the guinea pig lung for up least 60 days after RSV inoculation [70], subsequent studies showed that outbred Cam Hartley guinea pigs could harbor replicating virus for at least 60-100 days after inoculation, in association with nonspecific airway hyperresponsiveness (AHR) and chronic airway inflammation (physiological and pathological hallmarks of asthma) [24,30]. However, in subsequent work, we noted that viral persistence on its own is not sufficient to produce asthmalike changes in the lungs, as inbred, ''allergy-resistant'' strain 2 guinea pigs can also develop persistent RSV lung infections but these animals do not get AHR or chronic airway inflammation in association with virus persistence [71].…”
Section: Rsv and Pediatric Asthma: Have We Found The Missing Link?mentioning
confidence: 96%